THE ESOTERIC CONCEPT OF TAJALLIYAT IN ADAM’S CREATION: AN ANALYSIS OF THE JAVANESE TAFSIR FAYD AL-RAHMAN BY KIAI SALIH DARAT - Zennanta Agustia; Muhammad Ainur Rohman; M. Irfan Riyadi; Muhimmatul Mukaromah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2025)
The concept of tajalliyat is often derived from non-Nusantara Sufi scholars and referenced in non-tafsir works such as Ibn al-Arabi’s Futuhat al-Makkiyyah. However, the Javanese tafsir Fayd al-Rahman explicitly presents tajalliyat in the story of Adam’s creation. In Sufi tradition, tajalliyat is closely related to the concept of insan kamil (the Perfect Human). This study explores both concepts and their interrelation in Fayd al-Rahman using a thematic approach and content analysis. The findings reveal that tajalliyat in Adam’s creation refers to the manifestation of God’s Names and Attributes within Adam’s essence, reflecting the Divine through the expression ana huwa la huwa (“He is, yet not He”). Meanwhile, insan kamil is symbolized through Adam’s honor as khalifah, adorned with the taj al-karamah, libas al-sa‘adah, and nitaq al-qurbah. Their connection is interpreted through epistemological, ontological, and cosmic reasoning, showing tajalliyat as the path and insan kamil as its peak. Thus, Adam is portrayed as the embodiment of insan kamil manifested through divine tajalliyat.